Strategi Implementasi Program Gerakan Literasi Sekolah Berdasarkan Evaluasi Komprehensif Di SMP Bina Insani Kota Bogor - Suwarni, Suwarni; Hendarman, Hendarman; Herfina, Herfina (Universitas Pakuan, 2024)
STRATEGY FOR IMPLEMENTATION OF SCHOOL LITERACY MOVEMENT PROGRAM BASED ON A COMPREHENSIVE EVALUATION AT SMP BINA INSANI KOTA BOGOR This research aimed to analyze the implementation of the School Literacy Movement (SLM) program at SMP Bina Insani Kota Bogor using evaluative research methods with the CIPPO model which included the components of context, input, process, product and outcomes. The aspects evaluated were those that had gone well and those that were still not optimal as a basis for policy making in the following years. Data collection was carried out through techniques of interview, observation and documentation studies. The informants were determined using purposive sampling. The data analysis technique used the Miles and Huberman model, namely data reduction, data display and conclusions. The results of the research showed that of the 4 aspects in the context component evaluated, each received